2020
DOI: 10.1042/bsr20201524
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lncRNA-Ang362 and prognosis of patients with coronary heart disease after percutaneous coronary intervention

Abstract: The severity and complexity evaluation of coronary artery disease in patients with coronary heart disease (CHD) require objective and accurate prognosis indexes. We assessed the relationship between lncRNA-Ang362 and prognosis of CHD patients after percutaneous coronary intervention (PCI). Clinical follow-up data of CHD patients were prospectively collected. LncRNA-Ang362 levels were detected by real-time quantitative polymerase chain reaction. Survival rate was calculated by the Kaplan-Meier method, and risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…CAD has a relatively high morbidity and mortality, posing a severe threat to human health, and increases the burden of the family and society. Currently, commonly, surgical treatment and pharmacotherapy are used clinically; among them, surgical treatment has a higher requirement of tolerance by the patients and readily induce vessel nerve reflex, and some patients are not satisfied with treatment efficacy [8]. The development of CAD is closely associated with blood lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…CAD has a relatively high morbidity and mortality, posing a severe threat to human health, and increases the burden of the family and society. Currently, commonly, surgical treatment and pharmacotherapy are used clinically; among them, surgical treatment has a higher requirement of tolerance by the patients and readily induce vessel nerve reflex, and some patients are not satisfied with treatment efficacy [8]. The development of CAD is closely associated with blood lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LncRNA CARMEN and LncRNA fendrr are associated with embryonic heart development ( 18 , 19 ). LncRNA-Ang362 may be associated with prognosis after coronary stenting (percutaneous coronary intervention) for CHD ( 20 ). Increased expression of LncRNA GAS5 was found in plaques of atherosclerotic individuals, and the mechanism may be related to exosome regulation of macrophage and endothelial cell apoptosis in atherosclerotic plaques ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes derived from MSCs carry a number of bioactive substances, such as proteins, miRNAs and lncRNAs, and play an important role in the treatment of cardiovascular diseases, such as atherosclerosis ( 18 , 43 , 44 ). A high expression level of lncRNA-Ang362 was shown to lead to a poor prognosis in patients with CAD ( 45 ). Moreover, Mao et al ( 46 ) demonstrated that MSC-derived exosomal lncRNA Krüppel-like factor 3 antisense RNA 1 alleviated the development of myocardial infarction via the miR-138-5p/Sirtuin-1 axis ( 46 ).…”
Section: Discussionmentioning
confidence: 99%